A Literature Review on the Impact of Project Based Learning and Socio Demographic Variables on Academic Outcomes - Alvarez, Chardemie; Abella, Magdalina; Macaraeg, Jan (JPAIR Institutional Research, 2026)
This literature review examines how Project-Based Learning (PBL) influences students’ academic outcomes and how socio-demographic variables moderate these effects. Grounded in constructivist theory, PBL is a learner-centered approach that engages students in sustained inquiry, collaboration, and real-world problem solving, contrasting with lecture-based instruction that often emphasizes content transmission. The chief objective of this review is to synthesize empirical evidence on PBL’s impact on academic achievement, scientific literacy, higher-order thinking, and content mastery, while analyzing the moderating roles of age, gender, and socioeconomic status (SES). Using a narrative review method, peer-reviewed studies and meta-analyses from multiple academic databases (2010-2025) were examined and organized thematically across instructional outcomes and demographic influences. Results indicate that PBL generally improves achievement, cognitive engagement, inquiry skills, and long-term retention, with meta-analytic findings. However, outcomes vary across student groups: SES strongly predicts access to resources and readiness for inquiry, younger learners often require greater scaffolding for self-regulation, and gendered participation patterns may affect roles and engagement in collaborative tasks. The review concludes that PBL is a robust strategy for promoting deep learning and 21st-century competencies, but equitable benefits require inclusive design, differentiated supports, culturally responsive pedagogy, and adequate resource allocation.